Quickly Understanding of Needs and Issues of Undergraduate University Students in Listening Comprehension: A Need Analysis to develop Assisted-Social Media Learning Material - Syofianis Ismail; Erna Nawir (UIR Press, 2023)
Using social media in teaching listening requires creativity and modification in order to be suitable for learning. The aim of this research is to identify the learners' need for developing assisted-social media learning material in listening comprehension course at the Islamic University of Riau, Indonesia. The study involved undergraduate students taking listening comprehension subject who were selected through cluster random sampling. Along with the students, 5 lecturers were also involved. The instruments used in this study were questionnaire, interviews guide, and observation sheet. The questionnaire was centered on two main categories: Target need analysis and learning need analysis, drawing on the theoretical framework of Hutchinson and Waters (1987). Both analysis results revealed that the challenges faced by students while learning listening comprehension with the help of social media have a notable influence, mainly because of the discrepancy between the anticipated methods of learning and the actual internal factors that drive students to acquire effective listening skills. This situation is likely to contribute to the enhancement of their speaking abilities to meet their specific goals. As a result, meeting these goals requires additional support in terms of psychological, motivational, and material aspects. Overall, these findings provide valuable insights for designing and developing a tailor-made English learning material assisted by social media that meets the specific needs of the learners in the future particularly in listening comprehension course.